2009
DOI: 10.1093/jxb/erp256
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine oxidase activity contributes to sustain maize leaf elongation under saline stress

Abstract: The possible involvement of apoplastic reactive oxygen species produced by the oxidation of free polyamines in the leaf growth of salinized maize has been studied here. Salt treatment increased the apoplastic spermine and spermidine levels, mainly in the leaf blade elongation zone. The total activity of polyamine oxidase was up to 20-fold higher than that of the copper-containing amine oxidase. Measurements of H(2)O(2), *O(2)(-), and HO* production in the presence or absence of the polyamine oxidase inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 83 publications
(118 reference statements)
4
57
0
1
Order By: Relevance
“…Both DAO and PAO are localized to the cytoplasm and cell wall and are involved in production of the hydrogen peroxide required for cell wall stiffening (Cona et al, 2003; (Figure 1). These enzymes seem to contribute to changes in growth during salt stress since increased PAO accumulation in the expansion zone of maize leaves enhanced both ROS accumulation and elongation (Rodríguez et al, 2009;Shoresh et al, 2011). Moreover, high salt (400 mM NaCl) or ROS application induces DAO activity in the leaves and roots of the halophyte Mesembryanthemum crystallinum further implicating that these enzymes play a role in salt stress (Shevyakova et al, 2006).…”
Section: Polyamines: One Of the Prominent Regulators In Ros Homeostasmentioning
confidence: 98%
“…Both DAO and PAO are localized to the cytoplasm and cell wall and are involved in production of the hydrogen peroxide required for cell wall stiffening (Cona et al, 2003; (Figure 1). These enzymes seem to contribute to changes in growth during salt stress since increased PAO accumulation in the expansion zone of maize leaves enhanced both ROS accumulation and elongation (Rodríguez et al, 2009;Shoresh et al, 2011). Moreover, high salt (400 mM NaCl) or ROS application induces DAO activity in the leaves and roots of the halophyte Mesembryanthemum crystallinum further implicating that these enzymes play a role in salt stress (Shevyakova et al, 2006).…”
Section: Polyamines: One Of the Prominent Regulators In Ros Homeostasmentioning
confidence: 98%
“…For instance, salt stress increased apoplastic spermine and spermidine levels, mainly in the leaf blade elongation zone. Polyamine oxidase activity provides significant production of reactive oxygen species in the apoplast, which contributes to 25-30 % of maize leaf blade elongation (Rodríguez et al 2009). …”
Section: Apoplastic Acidificationmentioning
confidence: 99%
“…In another work, Tisi et al (2012) shown to be associated with biotic or abiotic stress response. Rodríguez et al (2009) reported that under saline stress, oxidation of higher PAs by PAOs helped to sustain leaf elongation. H 2 O 2 produced through the PA oxidation has been also reported to be involved in hypersensitivity reaction (HR) that can render plants more tolerant to bacterial pathogen (Fu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%